Effect of Denture Tooth Material on Load Transmission Under Denture Bases - Ramin Mosharraf; Farzad Ziaei; Mahsa Abbasi (Tehran University of Medical Sciences, 2018)
Objectives: Pressure transmission under denture bases can vary depending on the denture tooth material. The aim of the present study was to evaluate pressure transmission under denture bases using denture teeth of different materials in direct and indirect tooth contacts. Materials and Methods: In this in-vitro study, the pressure transmission generated by five types of denture teeth, including ceramic, nanocomposite, composite-acrylic resin, cross-linked acrylic resin, and polymethyl methacrylate (PMMA), under direct and indirect pressures was evaluated (n=10). The maximum pressure (MPa) was measured using a strain gauge. Data were statistically analyzed with one-way analysis of variance (ANOVA; α=0.05). Results: The denture tooth material had a significant effect on pressure transmission under denture bases (P<0.001). Under direct load, ceramic and PMMA teeth exhibited the maximum and minimum pressures, respectively, contrary to indirect load (P<0.001). Conclusions: Pressure transmission under denture bases significantly varies with the use of different denture tooth materials. Acrylic teeth could be the most favorable choice to reduce the pressure beneath denture bases. Nanocomposite and acrylic resin-composite teeth may be used as alternatives.